2010
DOI: 10.1103/physreve.81.036707
|View full text |Cite
|
Sign up to set email alerts
|

Phase-field modeling by the method of lattice Boltzmann equations

Abstract: In this paper, at first, a lattice Boltzmann method for binary fluids, which is applicable at low viscosity values, is developed. The presented scheme is extension of the free-energy-based approach to a multi-relaxation-time collision model. Various benchmark problems such as the well-known Laplace law for stationary bubbles and capillary-wave test are conducted for validation. As an appealing application, instability of a rising bubble in an enclosed duct is studied and irregular behavior of the bubble is obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
116
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 58 publications
0
116
0
Order By: Relevance
“…the leading order of the intermolecular forcing terms was reduced from O (1) to O(u) [87]). Although this model is more robust than most of the previous LBMs, it is restricted to density ratios up to approximately 15 [138]. The derivation and more details of the mean-field theory model can be found in [87].…”
Section: Mean-field Theory Modelmentioning
confidence: 99%
“…the leading order of the intermolecular forcing terms was reduced from O (1) to O(u) [87]). Although this model is more robust than most of the previous LBMs, it is restricted to density ratios up to approximately 15 [138]. The derivation and more details of the mean-field theory model can be found in [87].…”
Section: Mean-field Theory Modelmentioning
confidence: 99%
“…Nevertheless, the model of Zheng et al was found to be restricted to density-matched binary fluids and unable to simulate multiphase flows with noticeable density differences [26]. The model of Lee et al has successfully reproduced some multiphase flows at large density ratio, but the numerical algorithm is complex and its computational efficiency may be low because the numerical implementation involves the discretization of many derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Then, a revised lattice Boltzmann equation to recover the CH equation is proposed by Zheng et al (2006), which has relatively high efficiency and stability. However, this model is proved to be restricted to densitymatched binary fluids (Fakhari and Rahimian, 2010). Recently, a modified new model considering the local density variation is developed by Shao et al (2014).…”
Section: Introductionmentioning
confidence: 99%